Inventory and distribution of the Annonaceae along elevation gradient on Mount Cameroon - Bele, M.Y.; Focho, D.A.; Egbe, E.A.; Chuyong, G.B. (2011)
This work was carried out on Mount Cameroon, South West Region of Cameroon. It focused on producing an inventory and distribution of Annonaceae along the elevation gradient on the mountain. As a matter of fact, how Annonaceae flora change along an elevation gradient has never been studied for Mount Cameroon. The Complete Census Method was used. Twelve sites, located at three elevation categories: low (lowland: sea level to 700 m), mid (submontane: 800 to 1800 m), and high (montane: 2200 to 3500 m) were investigated. At each site, 8 transects of 500 m × 10 m were sampled and all the Annonaceae species enumerated. To supplement the information gathered on measured plots and to generate a complete list of target species, plotless sample method was used. This entailed the collection of materials along footpaths and within particular habitats such as ravines, seasonal streams, and disturbed areas. A total of 49 species in 21 genera including climbers, shrubs and trees were collected and identified from both plot and plotless samples. Low and mid elevations were rich in Annonaceae with 37 species in 17 genera and 31 species in 16 genera, respectively. The family was nearly absent from high elevation with only one species. Sixteen species in 10 genera were restricted to low elevation and 11 species in 8 genera confined to the mid elevation. Only Uvariodendron connivens was abundantly found at both low and mid elevations. Three species were frequent and confined to low elevation only. One and five species appeared occasionally and were restricted to low and mid elevations, respectively. 23, 18 and 1 species were rare at low, mid and high elevations respectively. Low elevation showed a higher species diversity (H' = 2.65) than the mid elevation (H' = 0.48). The high elevation with two individuals in a single species was the least diverse (H' = 0.15). The species were more even in their abundance distribution within the low elevation (J = 0.76) than in the mid elevation (J = 0.15).